Anmeldelse af Carl Widstrand (ed.), Multinational Firms in Africa. African Institute for Economic Development and Planning, Dakar, Scandinavian Institute of African Studies, Uppsala, Uppsala 1975. 425 sider, ca. 130 kr. - Ougaard:, Morten (Politica, 1977)
-